LabVIEW virtual instrument for zone penetration studies in flow-based analytical systems - Kuljanin Aleksandra (Serbian Chemical Society, 2021)
In the flow method development, zone penetration studies are usually conducted as a part of the initial screening phase. A lack of an appropriate tool can keep these studies on the level of rough estimations. The developed LabVIEW virtual instrument (VI) which processes peak signals and calculates the overlapping area and fundamental peak-related parameters was used for the calculations in experiments that are modelling sample and reagent plug interaction within liquid conduits. The reliability of the predictions was initially confirmed on the artificial data set based on thirty-six files covering all the different types of cases that can be foreseen. To continue, the volumes of model solutions, propelling flow rate, and the coil length in the sequential injection analysis system, were varied by following the Box–Behnken response surface design. In three examples, it is demonstrated how the VI can help the planning of further experiments in the range which ensures the efficient zone overlapping, the economic exploitation of reagent plug and the adequate dispersion. The application of the VI is not limited just to the flow-based chemistry, it can also be used in spectroscopy and chromatography. In order to use the graphical user interface, it is not necessary to have the LabVIEW program installed.